Butterflies (Lepidoptera: Papilionoidea) of northwestern and western Crete (Greece) in early July, with the finding of new larval host plant for Lampides boeticus: Surveying the distribution of diurnal butterflies of western Crete - Šturm, Luka (ENTOMOLOGIA HELLENICA, 2022)
During the summer of 2021 northwestern and western areas of the Greek island of Crete were surveyed, in order to confirm certain observations of the diurnal butterfly fauna of the island. Research was focused especially on the unsurveyed north-western parts of the island, as well as surveying the species that are extending their areal (Cacyreus marshalli (Butler), Lampides boeticus (L.)). From 47 species reported from the island, 23 were observed. The surveys were all carried out during an especially hot and dry weather period (30-37 °C), between 30th of June and 6th of July. Additionally, a new larval host plant for L. boeticus was confirmed, as oviposition of females on Campsis radicans (Seem.) was observed on several occasions.